Building customer loyalty: The effect of experimental state, the value of shopping, trust and perceived value of service on online clothes shoping. - Molinillo-Jiménez, Sebastián; Gómez-Ortiz, Beatriz; Pérez-Aranda, Javier Ramón; Navarro-García, Antonio (Sage, 2017)
Based on consumer behavior theories, the aim of this study is to provide a model supported by empirical evidence in order to improve knowledge of the antecedents of loyalty to online clothing retailers. The model has been verified through partial least squares analysis of the data obtained from a survey of a sample of 412 online clothing shoppers. The results show that, firstly, the affective and cognitive experiences have a positive effect on the degree of satisfaction, and the affective experiences also have a positive impact on trust. Secondly, it has been demonstrated that consumer satisfaction with online clothing retailers can be increased by both the hedonic and utilitarian values of shopping. Thirdly, an indirect relationship has been established between satisfaction and loyalty through trust and perceived value of service. These findings can improve our understanding of the determinants of online consumer loyalty. Discussion and implications are provided.
Copyright de los autores.
Keywords: Consumidores - Conducta; Comercio electrónico; Marketing en Internet; Internet shopping; Consumer behavior; Retail; Loyalty; Clothing